The ins and outs of eukaryotic viruses: Knowledge base and ontology of a viral infection. - Chantal Hulo; Patrick Masson; Edouard de Castro; Andrea H Auchincloss; Rebecca Foulger; Sylvain Poux; Jane Lomax; Lydie Bougueleret; Ioannis Xenarios; Philippe Le Mercier (PLoS ONE, 2017)
Viruses are genetically diverse, infect a wide range of tissues and host cells and follow unique processes for replicating themselves. All these processes were investigated and indexed in ViralZone knowledge base. To facilitate standardizing data, a simple ontology of viral life-cycle terms was developed to provide a common vocabulary for annotating data sets. New terminology was developed to address unique viral replication cycle processes, and existing terminology was modified and adapted. The virus life-cycle is classically described by schematic pictures. Using this ontology, it can be represented by a combination of successive terms: "entry", "latency", "transcription", "replication" and "exit". Each of these parts is broken down into discrete steps. For example Zika virus "entry" is broken down in successive steps: "Attachment", "Apoptotic mimicry", "Viral endocytosis/ macropinocytosis", "Fusion with host endosomal membrane", "Viral factory". To demonstrate the utility of a standard ontology for virus biology, this work was completed by annotating virus data in the ViralZone, UniProtKB and Gene Ontology databases.